Episodic positive selection in the evolution of avian toll-like receptor innate immunity genes. - Catherine E Grueber; Graham P Wallis; Ian G Jamieson (PLoS ONE)
Toll-like receptors (TLRs) are a family of conserved pattern-recognition molecules responsible for initiating innate and acquired immune responses. Because they play a key role in host defence, these genes have received increasing interest in the evolutionary and population genetics literature, as their variation represents a potential target of adaptive evolution. However, the role of pathogen-mediated selection (i.e. episodic positive selection) in the evolution of these genes remains poorly known and has not been examined outside of mammals. A recent increase in the number of bird species for which TLR sequences are available has enabled us to examine the selective processes that have influenced evolution of the 10 known avian TLR genes. Specifically, we tested for episodic positive selection to identify codons that experience purifying selection for the majority of their evolution, interspersed with bursts of positive selection that may occur only in restricted lineages. We included up to 23 species per gene (mean = 16.0) and observed that, although purifying selection was evident, an average of 4.5% of codons experienced episodic positive selection across all loci. For four genes in which sequence coverage traversed both the extracellular leucine-rich repeat region (LRR) and transmembrane/intracellular domains of the proteins, increased positive selection was observed at the extracellular domain, consistent with theoretical predictions. Our results provide evidence that episodic positive selection has played an important role in the evolution of most avian TLRs, consistent with the role of these loci in pathogen recognition and a mechanism of host-pathogen coevolution.